Maternal and Child Health Services Mobile Application Prototype: A Case Study of Puskesmas Sungai Duren Muara Enim Regency - Rasmila, Rasmila; Amalia, Rahayu; Adryansyah, Muhammad Rizqi Hidayah; Juniar, Kanero (Journal of Information System and Informatics, 2025)
The Sungai Duren Community Health Center (Puskesmas), located in Muara Enim Regency, provides essential maternal and child health services. Currently, patient registration and data management are conducted manually using patient data books, leading to inefficiencies, errors, and data loss. This research aims to develop a UI/UX mobile application that enhances maternal and child health services at the health center. The study employs the Design Sprint 2.0 methodology, a rapid, iterative, and user-centered design approach consisting of five stages: Understand, Define, Decide, Prototype, and Test. The design of the application was created using Figma, and its effectiveness was evaluated through usability testing, using the System Usability Scale (SUS) and Net Promoter Score (NPS). The results of the study show that the application improves operational efficiency, enhances user satisfaction, and provides better access to health data, demonstrating the potential for scalable and replicable solutions in rural and underserved healthcare settings.